Advances in Culture Theory from Psychological Anthropology (Culture, Mind, and Society, 2018)
This edited volume provides a long-overdue synthesis of the current directions in culture theory and represents some of the very best in ongoing research. Here, culture theory is rendered as a jigsaw puzzle: the book identifies where current research fits together, the as yet missing pieces, and the straight edges that frame the bigger picture. These framing ideas are two: Roy D'Andrade's concept of lifeworlds-adapted from phenomenology yet groundbreaking in its own right-and new thinking about internalization, a concept much used in anthropology but routinely left unpacked. At its heart, this book is an incisive, insightful collection of contributions which will surely guide and support those who seek to further the study of culture.